Pengaruh Intervensi Antenatal Education Menggunakan Media Digital Tehadap Perilaku Kesehatan Dan Kondisi Kesehatan Ibu: Literatur Review - Ni Wayan Ariyani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2018)
One of the determinants of maternal mortality is the low knowledge of mothers about pregnancy, childbirth and the puerperium. Antenatal education using digital media is one method that needs to be developed to improve maternal knowledge and health. The use of digital media has greatly increased by the community.The purpose of this study is to find out about the methods and results of antenatal education using digital media.Search through two data based articles, Pubmed and Google Schoolar. In addition to the two data bases, searches were also carried out on the literature list of articles. Articles were selected from 2000 to October 2017, using an intervention design, both quantitative and qualitative.The results of a review of 11 studies show that antenatal education interventions through digital media significantly influence changes in knowledge. Interventions aimed at changing behavior find inconsistent results. Interventions aimed at changing clinical conditions do not show no change.Conclusion The results of the study show that digital media-based antenatal education interventions affect knowledge, but do not provide consistent results on behavioral and clinical variables.